QUESTIONS WITH QUESTION WORDS ABOUT PLACES IN GERMAN AND VIETNAMESE FROM SYNTACTIC PERSPECTIVE - Thuy, Le Thi Bich (VNU Journal of Foreign Studies, 2020)
This paper points out the similarities and differences of questions with question words about places in German and Vietnamese seen from syntactical perspective. For this purpose, those questions in literary works written in German and Vietnamese and their translations are analysed to identify their syntactic patterns. The results show there is only one question structure in German: QW + V + S (+ O)? (elliptical construction: QW?) whereas question structures in Vietname are far more varied. This is because the two languages belong to two different types of languages: German is an inflectional language while Vietnamese is an isolating one whose word order plays a very important role.